2006
DOI: 10.1038/sj.ijo.0803362
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Comparison of body fatness measurements by BMI and skinfolds vs dual energy X-ray absorptiometry and their relation to cardiovascular risk factors in adolescents

Abstract: The figure legend to Figure 1 of the above paper was published incorrectly.The correct legend is given below. The authors would like to apologise for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of the influencing factors for CVD, Steinberger et al [8] collected the sample data set of seven cities in North Carolina from 1999 to 2001, fitted the three-stage Bayesian hierarchical model, and concluded that the higher the concentration of PM2.5, the greater the probability of residents suffering from CVD. Ferrandiz et al [9] used the Spanish Rapid Inquiry System (RIF) to conduct more precise and systematic exposure measurement and disease data collection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the influencing factors for CVD, Steinberger et al [8] collected the sample data set of seven cities in North Carolina from 1999 to 2001, fitted the three-stage Bayesian hierarchical model, and concluded that the higher the concentration of PM2.5, the greater the probability of residents suffering from CVD. Ferrandiz et al [9] used the Spanish Rapid Inquiry System (RIF) to conduct more precise and systematic exposure measurement and disease data collection.…”
Section: Literature Reviewmentioning
confidence: 99%